Activation of Dopamine D1-D2 Receptor Complex Attenuates Cocaine Reward and Reinstatement of Cocaine-Seeking through Inhibition of DARPP-32, ERK, and ΔFosB - Hasbi, Ahmed; Perreault, Melissa L.; Shen, Maurice Y. F.; Fan, Theresa; Nguyen, Tuan; Alijaniaram, Mohammed; Banasikowski, Tomek J.; Grace, Anthony A.; O'Dowd, Brian F.; Fletcher, Paul J.; George, Susan R. (Frontiers in Pharmacology, 2018)
A significant subpopulation of neurons in rat nucleus accumbens (NAc) coexpress dopamine D1 and D2 receptors, which can form a D1-D2 receptor complex, but their relevance in addiction is not known. The existence of the D1-D2 heteromer in the striatum of rat and monkey was established using in situ PLA, in situ FRET and co-immunoprecipitation. In rat, D1-D2 receptor heteromer activation led to place aversion and abolished cocaine CPP and locomotor sensitization, cocaine intravenous self-administration and reinstatement of cocaine seeking, as well as inhibited sucrose preference and abolished the motivation to seek palatable food. Selective disruption of this heteromer by a specific interfering peptide induced reward-like effects and enhanced the above cocaine-induced effects, including at a subthreshold dose of cocaine. The D1-D2 heteromer activated Cdk5/Thr75-DARPP-32 and attenuated cocaine-induced pERK and ΔFosB accumulation, together with inhibition of cocaine-enhanced local field potentials in NAc, blocking thus the signaling pathway activated by cocaine: D1R/cAMP/PKA/Thr34-DARPP-32/pERK with ΔFosB accumulation. In conclusion, our results show that the D1-D2 heteromer exerted tonic inhibitory control of basal natural and cocaine reward, and therefore initiates a fundamental physiologic function that limits the liability to develop cocaine addiction.